Cytological Deterioration of Bitter Gourd (Momordica charantia L.) Pollen During Storage and Its Impact on Effectiveness for Seed Production - Kusumastuti, Hamiddah Intan; Widajati, Eny; Palupi, Endah Retno (Department of Agronomy and Horticulture, IPB University, 2025)
Pollen storage plays an important role in the hybrid seed production of bitter gourd, but a primary challenge is the rapid decline in pollen viability. This research aimed to investigate the mechanisms of bitter gourd pollen deterioration during storage and to assess the effectiveness of stored pollen for hybrid seed production. The study was conducted at the Leuwikopo Research Station, IPB University, from September 2018 to June 2021. Bitter gourd pollen was collected at anthesis and stored in a deep freezer at -21±3ºC. Pollen viability was observed at 0, 2, 4, 6, 8, 10, and 12 weeks after storage (WAS), while pollen ultrastructure was examined at 0, 4, 8, and 12 WAS using a transmission electron microscope. The stored pollen was then used for pollination, observations were made on fruit set, seed set, and seed quality. The viability of bitter gourd pollen declined rapidly following dehydration before storage. The declining pollen viability during storage was due to the degeneration of the intine, followed by mitochondrial deterioration. The cristae became disorganised, leading to the dissolution of the cristae and outer membrane of mitochondria. Storing the pollen in a deep freezer (-21±3ºC) after dehydration did not prevent a further decline in pollen viability. Bitter gourd pollen stored for more than 2 weeks at -21±3ºC is ineffective for seed production. Cucurbit pollen remains viable for only two weeks; thus, fresh pollen is more practical for hybrid seed production. Development of more effective pollen storage methods is necessary to prolong pollen viability and enhance breeding efficiency.